Assessment of Critical Success Factors Transformation in ERP Projects. Issue 7 (2016) - Pecherskaya, Evelina P.; Averina, Lyudmila V.; Kamaletdinov, Yuri A.; Tretyakova, Natalia V.; Magomadova, Tamilla L.
No abstract available